The complete product of annihilatingly unique digraphs - C. S. GAN (International Journal of Mathematics and Mathematical Sciences)
Let G be a digraph with n vertices and let A(G) be its adjacency matrix. A monic polynomial f(x) of degree at most n is called an annihilating polynomial of G if f(A(G))=0. G is said to be annihilatingly unique if it possesses a unique annihilating polynomial. Difans and diwheels are two classes of annihilatingly unique digraphs. In this paper, it is shown that the complete product of difan and diwheel is annihilatingly unique.